Determination of zinc in rice grains using DTZ staining and ImageJ software - Rômulo F. Duarte (2018)
© 2015 Elsevier Ltd. Dithizone (DTZ) staining is a rapid, simple, and inexpensive method that allows the histochemical localization of Zn. In this study, we evaluated genotypic variation in Zn concentration in brown rice grown in the field using atomic absorption spectrophotometer (AAS) as DTZ staining quantified using ImageJ software. We used dehusked grains from upland rice accessions widely cultivated in Brazil. The DTZ staining showed that the concentration of Zn varied within and between rice grains. The staining intensity index (Y) provided differences in localization of Zn across the grain regions. Zn concentration in brown rice varied in multiple regression analysis, showing major differences in index weighted by stained area of each region (YAW) for the embryo, endosperm, and aleurone, especially in the endosperm and aleurone regions due to a large portion of the area in the kernel. The total YAW among rice accessions was positively correlated with Zn concentration in grains by chemical analysis. The DTZ staining associated with imageJ software is a promising to estimate Zn concentration in different grain tissues. Thus, this method may be useful for rapid screening of rice germplasms.